Evaluation of a Second-Generation Microtransesophageal Echocardiography Transducer and Software. (October 2014) - Frank, Lowell H.; Chelliah, Anjali; Sable, Craig A.
Background: Transesophageal echocardiographic imaging of small infants has been limited because of equipment size. A newer miniaturized transducer has allowed for the imaging of even the smallest patients but has been limited by intermittent poor image quality because of hardware durability. A second generation of the transducer was developed to address this problem. The aim of this study was to evaluate the performance and durability of the second-generation transducer over multiple uses and to compare the image quality from the modified transducer and new software preset to the original transducer. Methods: Patients undergoing transesophageal echocardiography (TEE) based on clinical indications with the original or second-generation transducers were included in the study. All studies were reviewed for image quality and unacceptable image degradation, which was defined as imaging quality inadequate for clinical use. Study review was performed by two echocardiographers. Results: Using the original transducer, 37 studies were performed with a mean patient weight of 3.46 ± 0.89 kg (range 2.1-5.7). Using the second-generation transducer, 65 studies were performed with a mean patient weight of 4.87 ± 2.05 kg (range 2.2-13.8). Image quality was clinically inadequate in 8 of the 35 studies with the original transducer and in zero with the second generation ( P < .0001). Conclusions: The second-generation transducer allows for effective use of TEE even in the smallest infants and avoids the mechanical failures associated with the first-generation release.